Modeling of Hydrodynamic Cavitation Reactors: Reflections on Present Status and Path Forward - Ranade, Vivek V. (ACS Engineering Au, 2022)
Hydrodynamic cavitation (HC) is finding ever increasing applications in water, energy, chemicals, and materials sectors. HC generates intense shear, localized hot spots, and hydroxyl radicals, which are harnessed for realizing desired physicochemical transformations. Despite identification of HC as one of the most promising technology platforms, its potential is not yet adequately translated in practice. Lack of appropriate models for design, optimization, and scale-up of HC reactors is one of the primary reasons for this. In this work, the current status of modeling of HC reactors is presented. Various prevailing approaches covering empirical, phenomenological, and multiscale models are critically reviewed in light of personal experience of their application. Use of these approaches for different applications such as biomass pretreatment and wastewater treatment is briefly discussed. Some comments on extending these models for other applications like emulsions and crystallization are included. The presented models and discussion will be useful for practicing engineers and scientists interested in applying HC for a variety of applications. Some thoughts on further advances in modeling of HC reactors and outlook are shared, which may stimulate further research on improving the fidelity of computational models of HC reactors.